Joubert syndrome with multiple pituitary hormone deficiency. Issue 4 (23rd April 2019) - Akcan, Nese; Bas, Firdevs; Poyrazoglu, Sukran; Bundak, Ruveyde
Abstract : Joubert syndrome (JS) and JS-related disorders are a group of developmental delay, multiple congenital anomalies and complex midbrain–hindbrain malformations. A few cases of JS with multiple pituitary hormone deficiency (MPHD) have been reported in literature. Here, we presented an unusual presentation of JS in a newborn with MPHD. This case is intended to draw attention to the rare association of JS and MDPH by increasing the awareness of this syndrome.